Experiments and nonlinear simulations of a rubber isolator subjected to harmonic and random vibrations. (7th July 2019) - Roncen, T.; Sinou, J.-J.; Lambelin, J.-P.
Abstract: This paper presents experiments and numerical simulations of a nonlinear rubber isolator subjected to both harmonic and broadband random excitations. Harmonic and broadband random excitations are performed experimentally in order to show the softening effect of the rubber isolator for high amplitudes of displacement and to show the temperature dependency of its mechanical properties. Firstly, the rubber isolator is modeled as a one degree-of-freedom system, whose stiffness and damping depend only on the amplitude of the relative displacement of the joint. The relationship between the stiffness and the damping versus the amplitude of the relative displacement of the rubber isolator is updated via experiments. Secondly, the Harmonic Balance Method (HBM) and the shooting method are presented and extended to take into account both harmonic and random excitations. A modification of the nonlinear methods is necessary in order to recover the information concerning the displacement amplitude. Moreover, for random excitations, a periodogram strategy is used to ensure a good estimate of the resulting Power Spectral Density (PSD). Finally, comparisons between experiments and simulations are undertaken. Good correlations are observed for harmonic and broadband random excitations, thus validating the modeling of the rubber isolator and the proposed nonlinear methodology. Highlights: Harmonic Balance Method (HBM) and shooting method for mechanical systems with stochastic excitations. Application for a rubber isolator subjected to harmonic and random vibrations. Comparisons between experiments and numerical simulations.